To What Extent Does Ericsson Adapt Their Organisational Culture When Opening A Branch in A New Culture? - Lea Christiane Neupauer; Daisy Mui Hung Kee; Helen Ghebregziabher; Jaska Leander Triem; Ida Annica Margareta Antonsson; Anshuman Singh; Danah Naji Alkhoudher; Rafael Alvin Susanto (International Journal of Applied Business and International Management, 2020)
Telefonaktiebolaget LM Ericsson (Ericsson) is a Swedish telecom company with branches all over the world. It is not a secret that a company with branches in several diverse cultures has to decide what extent the organization will go in adapting the host culture into the new branch. This essay will focus on Ericsson and a few cases on how well Ericsson decided to incorporate host cultures into their organization. The cases picked will mainly be in Asia due to the greater cultural difference between the Asian host culture and their European home culture.